3D printed hand-held refractometer based on laser speckle correlation. (July 2019) - Trivedi, Vismay; Mahajan, Swapnil; Joglekar, Mugdha; Chhaniwal, Vani; Zalevsky, Zeev; Javidi, Bahram; Anand, Arun
Highlights: Simple, accurate and sensitive method for measuring small changes in refractive index. Inexpensive approach employing the principle of Snell's law and speckle correlation. Compact device with small form factor. Hand-held device fabricated employing 3D printer. Only 1 ml of liquid is required for measurement purpose. Abstract: Measurement of very small refractive index changes is very important from a material's characterization point of view. This paper demosntrates a compact, simple and accurate technique for measuring refractive indices of transparent liquids, based on Snell's law and laser speckle correlation. Furthermore, considering the cutting-edge technology of 3D printing and its ability to enhance a technique's functionality by providing a sturdy framework, a 3D printed hand-held device for measurement of refractive indices is also demonstrated. The device measures very small change in refractive index by measuring the change in the objective speckle pattern arising due to the change in laser light passing the liquid solution, which is caused by the apparent shift of a point source. Change in the speckle pattern is presented in terms of correlation coefficient which is computed by comparing a speckle pattern corresponding to distilled de-ionized water with that of the speckle pattern corresponding to a liquid whose refractive index is to be measured. This change in speckle pattern is related to the change in concentration which in turn is related to refractive index of the liquid. The device can measure changes in refractive index as small as 0.00038 with an average error less than 4.5%.